Pengaruh edukasi kesehatan reproduksi remaja terhadap pengetahuan siswa siswi Kelas VII SMP Negeri 2 Pineleng Kabupaten Minahasa - Sutjiato, Margareth; Mongi, Thirsa; Lontoh, Esther (UNIVERSITAS SAM RATULANGI, 2025)
Background: Adolescent reproductive health is a crucial issue influencing physical, mental, and social well-being. Many adolescents still possess limited knowledge about reproductive health, including the risks of unsafe sexual behavior and sexually transmitted infections. Preliminary findings at SMP Negeri 2 Pineleng indicated that most students lacked understanding of reproductive health and had never received education from health professionals. Aim: To determine the effect of reproductive health education on the knowledge level of students at SMP Negeri 2 Pineleng, Minahasa Regency. Methods: This study employed a quasi-experimental design with a one-group pre-test and post-test approach. A total of 30 seventh-grade students were selected using total sampling. The intervention consisted of structured reproductive health education delivered through lectures, discussions, and leaflet media. Knowledge levels were assessed using a Guttman-scale questionnaire. Data were analyzed using a Paired Sample T-Test with a significance level of 0.05. Results: Prior to the intervention, all students (100%) demonstrated poor knowledge. After receiving the education, 96.67% achieved good knowledge levels. The Paired Sample T-Test yielded p = 0.000, indicating a statistically significant difference between pre-test and post-test scores. Conclusion: Reproductive health education significantly improves students’ knowledge of adolescent reproductive health. Structured educational interventions supported by visual media are effective in enhancing adolescents’ understanding and may help prevent reproductive health problems. Keywords: health education, adolescent reproductive health, knowledge, quasi-experiment.